Interrelation of Verbal and Visual Signs Effectively Increases Engagement in @barenbliss_id Instagram Posters - I Gusti Ayu Cintya Premasari; Ni Wayan Sukarini; I Komang Sumaryana (Pusat riset dan Inovasi Nasional, 2025)
This research discusses the semiotic signs used in the @barenbliss_id Instagram posters. This research aims to identify the verbal and visual signs used in Barenbliss Indonesia Instagram posters and explain how these signs shape consumer perception to increase brand engagement. This research used a qualitative descriptive method. The data were collected from two Instagram posters published by @barenbliss_id in November 2024. These posters were documented and analyzed by identifying their verbal and visual elements. Afterward, the interrelation of the signs to increase engagement was explained. Afterward, the interrelation of the signs to increased engagement was explained. The analysis applied Barthes’s semiotics theory and supported by Chandler’s signs framework. The findings of this research show that visual signs are more dominant than verbal signs, with a total of 13 visual signs and 7 verbal signs. The signs used are texts containing information about the product, bright and soft colors, images of the product, and models that help visually show the product’s use. The verbal and visual signs used on the posters are interrelated and complement each other. These results show that well-coordinated use of verbal and visual elements can effectively shape positive consumer perceptions and increase brand engagement.